Teaching by heart : one professor's journey to inspire - DeLong, Thomas (Boston Harvard Business Review Press, 2019)
"Teaching by Heart summarizes the author's key insights gained over 40 years of teaching. It illustrates how teachers can both lift people up and let them down. It proposes that the best teachers are also leaders, and the best leaders are also teachers. In examining how to lead and teach, author Thomas J. DeLong takes the reader inside his own head and heart. He notes that, as teachers, we often focus more on our inadequacies and failures than on our strengths and accomplishments. He deconstructs why this is so by dissecting and analyzing his own experiences. The book's goal is to help readers learn what makes a great teacher and to impart lessons about how teachers can create magic during a class session. To do this, the author analyzes the process of creating a curriculum, preparing for an 80-minute class, managing the 15 minutes before class begins, and evaluating the nature of the teaching experience. Along the way, he connects specific classroom behaviors with leadership issues--in organizations, teams, and one's own life. He also asks--and answers--some provocative questions, such as: What happens on multiple levels while I am teaching? What am I thinking and feeling as I process what students are thinking and feeling? How are my internal conversations affecting how I teach? How do I manage my biases, including having "favorite" students? Whether you're a teacher, student, business leader, or just someone fascinated by teaching, this book will instruct, entertain, and--like the best teachers--inspire"--
Includes index.
Keywords: Teaching; Leadership; Teachers; Instructional systems